(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This paper makes an appraisal of medical confidentiality under the cameroonian law. Hence, it examines the duty of confidentiality and how the principle of confidentiality operate in Cameroon? What are the justifications for medical confidentiality? How can medical confidentiality be breached? How is medical confidentiality terminated? Based on the ensuing above, the paper examines the origins and concept of medical confidentiality. It further investigates the justifications of medical confidentiality and circumstances which medical confidentiality comes to an end. Findings reveal that the duty of medical confidentiality remains sacrosanct principle in medical professional-patient secrecy relationship in Cameroon. This is buttressed by the need to preserve the moral and integrity of patients, re-enforce patient doctor trust. This duty is breached where information with the quality of confidentiality is being divulge, where the information given in confidence and an unauthorized use of information. The study presents redress through criminal, civil administration and disciplinary sanctions against the offender. However, medical confidentiality is not absolute but qualified in Cameron due to consent of the patient, medical experts, legal requirement and further medical research.